2015
DOI: 10.1021/acschembio.5b00615
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Targeting of a MicroRNA Associated with Hepatocellular Carcinoma

Abstract: Development of precision therapeutics is of immense interest, particularly as applied to the treatment of cancer. By analyzing the preferred cellular RNA targets of small molecules, we discovered that 5″-azido neomycin B binds the Drosha processing site in the microRNA (miR)-525 precursor. MiR-525 confers invasive properties to hepatocellular carcinoma (HCC) cells. Although HCC is one of the most common cancers, treatment options are limited, making the disease often fatal. Herein, we find that addition of 5″-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 35 publications
0
39
0
1
Order By: Relevance
“…Several groups also succeeded in the selective inhibition of miRNA processing by targeting the Drosha processing site of miRNA . Childs‐Disney et al reported that neomycin B and its derivative 5′‐azido neomycin B bind the Drosha processing site in the miR‐525 precursor. Neomycin B is an FDA‐approved drug and used for the prevention of HE and bacterial infections caused by cirrhosis.…”
Section: Drug Resistancementioning
confidence: 99%
“…Several groups also succeeded in the selective inhibition of miRNA processing by targeting the Drosha processing site of miRNA . Childs‐Disney et al reported that neomycin B and its derivative 5′‐azido neomycin B bind the Drosha processing site in the miR‐525 precursor. Neomycin B is an FDA‐approved drug and used for the prevention of HE and bacterial infections caused by cirrhosis.…”
Section: Drug Resistancementioning
confidence: 99%
“…Together with the fact that bacterial growth was inhibited and cell‐envelope stress was detected, this points to impairment of cell‐wall biosynthesis. Antifungal agents targeting the natural catalytic RNA of group I introns and more recently miRNA‐targeting compounds have been described. CGlcN is the first example of a compound that acts on a self‐cleaving ribozyme thus inhibiting bacterial growth.…”
Section: Figurementioning
confidence: 99%
“…Another approach will be to inhibit sRNA interfering with porin expression that is involved in drug translocation. Recently, a small molecule was used to target human microRNA (miR)À525 precursors as an anti-cancer strategy [110]. This promising discovery can be repeated in bacteria for manipulating sRNA levels, which may save the failing antibiotic therapies.…”
Section: Resultsmentioning
confidence: 99%